PP2A: The Achilles Heal in MDS with 5q Deletion - Sallman, David A.; Wei, Sheng; List, Alan (Frontiers in Oncology, 2014)
Myelodysplastic syndromes (MDS) represent a hematologically diverse group of myeloid neoplasms, however, one subtype characterized by an isolated deletion of chromosome 5q (del(5q)) is pathologically and clinically distinct. Patients with del(5q) MDS share biological features that account for the profound hypoplastic anemia and unique sensitivity to treatment with lenalidomide. Ineffective erythropoiesis in del(5q) MDS arises from allelic deletion of the ribosomal processing S-14 (RPS14) gene, which leads to MDM2 sequestration with consequent p53 activation and erythroid cell death. Since its approval in 2005, lenalidomide has changed the natural course of the disease. Patients who achieve transfusion independence and/or a cytogenetic response with lenalidomide have a decreased risk of progression to AML and an improved overall survival compared to non-responders. Elucidation of the mechanisms of action of lenalidomide in del(5q) MDS has advanced therapeutic strategies for this disease. The selective cytotoxicity of lenalidomide in del(5q) clones derives from inhibition of a haplodeficient phosphatase whose catalytic domain is encoded within the common deleted region on chromosome 5q, i.e., protein phosphatase 2A (PP2Acα). PP2A is a highly conserved, dual specificity phosphatase that plays an essential role in regulation of the G2/M checkpoint. Inhibition of PP2Acα results in cell cycle arrest and apoptosis in del(5q) cells. Targeted knockdown of PP2Acα using siRNA is sufficient to sensitize non-del(5q) clones to lenalidomide. Through its inhibitory effect on PP2A, lenalidomide stabilizes MDM2 to restore p53 degradation in erythroid precursors, with subsequent arrest in G2/M. Unfortunately, the majority of patients with del(5q) MDS develop resistance to lenalidomide over time associated with PP2Acα overexpression. Targeted inhibition of PP2A with a more potent inhibitor has emerged as an attractive therapeutic approach for patients with del(5q) MDS.